THE EFFECTS OF ISLAMIC SOCIAL REPORTING IN RGEC RELATIONSHIPS ON COMPANY’S VALUE - Erisa Putri Wardani; Puji Nurhayati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The company's value is an assessment of investors, customers, and stakeholders on the company's condition that could be seen based on the market price value of the company's stock. This study aims to find out the influence of Risk Profile, Good Corporate Governance (GCG), Earnings and Capital (RGEC) on the value of companies with Islamic Social Reporting (ISR) as a moderation variable. This study used panel data regression analysis techniques from the annual report of 12 Indonesian Islamic banks in the period 2015-2019. In this study used quantitative data obtained from the Indonesia Stock Exchange (IDX) website and each Islamic bank website. The results of this study could be concluded that the risk profile has a positive and significant effect on the company's value. In contrast, Good Corporate Governance (GCG), earnings, and capital have a negative and insignificant effect on the company's value. Then, the ISR moderation variable also unable to moderate the relationship between earnings and company values. The contributions of this research are expected to provide a portrait to stakeholders for decision making in investing. This study has limitations on selecting variables that used only four financial ratios and one moderation variable, and the period used was limited. For further research, suggests to using variables other than NPF, the proportion of the board of commissioners, ROE, CAR and ISR , therefore the research results are different and enhance a research period.